For the equation y 4y 4y 0 say you know guess y2

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: = 4v ￿ (t)e−2t − 8v (t)e−2t ￿￿ y2 (t) = v ￿￿ (t)e−2t − 2v ￿ (t)e−2t − 2v ￿ (t)e−2t + 4v (t)e−2t ￿￿ ￿ y 2 + 4y2 + 4y2 = Reduction of order y1 (t) = e−2t . For the equation y + 4y + 4y = 0 , say you know ￿￿ Guess ￿ y2 (t) = v (t)e −2t . ⇒ ⇒ ￿ y2 (t) = v ￿ (t)e−2t − 2v (t)e−2t ￿ 4y2 (t) = 4v (t)e−2t 4y2 (t) = 4v ￿ (t)e−2t − 8v (t)e−2t ￿￿ y2 (t) = v ￿￿ (t)e−2t − 2v ￿ (t)e−2t − 2v ￿ (t)e−2t + 4v (t)e−2t ⇒ ￿￿ y2 (t) = v ￿￿ (t)e−2t − 4v ￿ (t)e−2t + 4v (t)e−2t ￿￿ ￿ y 2 + 4y2 + 4y2 = Reduction of order y1 (t) = e−2t . For the equation y + 4y + 4y = 0 , say you know ￿￿ Guess ￿ y2 (t) = v (t)e −2t . ⇒ ⇒ ￿ y2 (t) = v ￿ (t)e−2t − 2v (t)e−2t ￿ 4y2 (t) = 4v (t)e−2t 4y2 (t) = 4v ￿ (t)e−2t − 8v (t)e−2t ￿￿ y2 (t) = v ￿￿ (t)e−2t − 2v ￿ (t)e−2t − 2v ￿ (t)e−2t + 4v (t)e−2t ⇒ ￿￿ y2 (t) = v ￿￿ (t)e−2t − 4v ￿ (t)e−2t + 4v (t)e−2t ￿￿ ￿ y 2 + 4y2 + 4y2 = Reduction of order y1 (t) = e−2t . For the equation y + 4y + 4y = 0 , say you know ￿￿ Guess ￿ y2 (t) = v (t)e −2t . ⇒ ⇒ ￿ y2 (t) = v ￿ (t)e−2t − 2v (t)e−2t ￿ 4y2 (t) = 4v (t)e−2t 4y2 (t) = 4v ￿ (t)e−2t − 8v (t)e−2t ￿￿ y2 (t) = v ￿￿ (t)e−2t − 2v ￿ (t)e−2t − 2v ￿ (t)e−2t + 4v (t)e−2t ⇒ ￿￿ y2 (t) = v ￿￿ (t)e−2t − 4v ￿ (t)e−2t + 4v (t)e−2t ￿￿ ￿ y 2 + 4y2 + 4y2 = Reduction of order y1 (t) = e−2t . For the equation y + 4y + 4y = 0 , say you know ￿￿ Guess ￿ y2 (t) = v (t)e −2t . ⇒ ⇒ ￿ y2 (t) = v ￿ (t)e−2t − 2v (t)e−2t ￿ 4y2 (t) = 4v (t)e−2t 4y2 (t) = 4v ￿ (t)e−2t − 8v (t)e−2t ￿￿ y2 (t) = v ￿￿ (t)e−2t − 2v ￿ (t)e−2t − 2v ￿ (t)e−2t + 4v (t)e−2t ⇒ ￿￿ y2 (t) = v ￿￿ (t)e−2t − 4v ￿ (t)e−2t + 4v (t)e−2t ￿￿ ￿ y 2 + 4y2 + 4y2 = Reduction of order y1 (t) = e−2t . For the equation y + 4y + 4y = 0 , say you know ￿￿ Guess ￿ y2 (t) = v (t)e −2t . ⇒ ⇒ ￿ y2 (t) = v ￿ (t)e−2t − 2v (t)e−2t ￿ 4y2 (t) = 4v (t)e−2t 4y2 (t) = 4v ￿ (t)e−2t − 8v (t)e−2t ￿￿ y2 (t) = v ￿￿ (t)e−2t − 2v ￿ (t)e−2t − 2v ￿ (t)e−2t + 4v (t)e−2t ⇒ ￿￿ y2 (t) = v ￿￿ (t)e−2t − 4v ￿ (t)e−2t + 4v (t)e−2t ￿￿ ￿ y2 + 4y2 + 4y2 = v ￿￿ e−2t Reduction of order y1 (t) = e−2t . For the equation y + 4y + 4y = 0 , say you know ￿￿ Guess ￿ y2 (t) = v (t)e −2t . ⇒ ⇒ ￿ y2 (t) = v ￿ (t)e−2t − 2v (t)e−2t ￿ 4y2 (t) = 4v (t)e−2t 4y2 (t) = 4v ￿ (t)e−2t − 8v (t)e−2t ￿￿ y2 (t) = v ￿￿ (t)e−2t − 2v ￿ (t)e−2t − 2v ￿ (t)e−2t + 4v (t)e−2t ⇒ ￿￿ y2 (t) = v ￿￿ (t)e−2t − 4v ￿ (t)e−2t + 4v (t)e−2t ￿￿ ￿ y2 + 4y2 + 4y2 = v ￿￿ e−2t 0= Reduction of order y1 (t) = e−2t . For the equation y + 4y + 4y...
View Full Document

This note was uploaded on 02/12/2014 for the course MATH 256 taught by Professor Ericcytrynbaum during the Spring '13 term at The University of British Columbia.

Ask a homework question - tutors are online